Problems of attracting investment resources in the activities of municipal property enterprises - Goel, Amit Kumar; Strygul, L.; Strygul, A. (ТОВ "Планета-Прінт", 2021)
The work is devoted to the study of the problem of formation of the resource base of financial support of enterprises of communal ownership and ways to transform investments into an effective tool for socio-economic development.

Робота присвячена дослідженню проблеми формування ресурсної бази фінансового забезпечення підприємств комунальної форми власності та шляхи перетворення інвестицій в ефективний інструмент соціально-економічного розвитку.
Keywords: financial support; investments; socio-economic development; international financial institutions; portfolio investments; direct